2018
DOI: 10.1016/j.nepr.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Does simulation enhance nurses' ability to assess deteriorating patients?

Abstract: Recognising and responding to patient deterioration has been identified as a key skill in nursing care to ensure that care is escalated for prompt, efficient management of the potentially critically ill patient. Simulation is one teaching strategy that has been established in nurse education as a method for enhancing skills. The objective was to explore the experiences of registered nurses to ascertain whether they perceived that simulation enhanced their skills in recognising the deteriorating patient. An exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 34 publications
3
29
0
3
Order By: Relevance
“…During the professional training in the simulation sessions, the nurses became more aware of the importance of vital sign measurements. This is in line with findings by Bliss and Aitken (). In particular, the respiratory rate was emphasized as significant, especially since the simulation sessions revealed that quite a few nurses tended to pay little attention to and overlook the respiratory rate.…”
Section: Discussionsupporting
confidence: 94%
“…During the professional training in the simulation sessions, the nurses became more aware of the importance of vital sign measurements. This is in line with findings by Bliss and Aitken (). In particular, the respiratory rate was emphasized as significant, especially since the simulation sessions revealed that quite a few nurses tended to pay little attention to and overlook the respiratory rate.…”
Section: Discussionsupporting
confidence: 94%
“…Simulation provides students with a safe environment to practice, where feedback is given and there is time to reflect (Bliss & Aitken, ). According to Lavoie and Clarke (), many options are available for simulation equipment, from low‐fidelity anatomical models used by students to practice injections or the insertion of a Foley catheter to high‐fidelity manikins that reproduce physiological functions, hence enhancing the realism and authenticity of the simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative advances in simulation techniques in baccalaureate nursing education have paved the way to support real-time-decision-making skill development in novice nurses, providing them with the tools to care for seriously ill older adults. Simulation-based teaching utilizes real-time decision making to develop nursing students' critical thinking and clinical reasoning skills in a safe and controlled environment (4,5). Branching simulation designs are effective pedagogies to teach real-time decision making in the care of older adults with a variety of chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%